RESISTANCE LEVEL OF Pseudomonas stutzeri AGAINST MERCURY AND ITS ABILITY IN PRODUCTION OF MERCURY REDUCTASE ENZYME - Purkan Purkan; Safita Nurmalyya; Sofijan Hadi (Molekul, 2016)
Mercury reductase is an enzyme that is able to reduce Hg2+ to Hg0 non toxic. This enzyme is usually produced by mercury resistant bacteria. The research wanted to determine the resistance of indigenous Pseudomonas stutzeri isolate toward mercury and to explore the mercury reductase activity which is produced by the bacteria. The results of resistance assay of the Pseudomonas stutzeri toward mercury ion showed that the isolate could survive in media containing HgCl2 up to a concentration of 80 µM. The bacteria could produce mercury reductase optimally at the 24th of fermentation time. The enzyme showed optimum activity at pH 7 and temperature of 45 oC